Prayer Oracle and Theophany: The Book of Habakkuk - Thompson, Michael E. W. (Tyndale bulletin, 1993)
Habakkuk comprises laments, prophetic and woe oracles, and psalm (prayer), but there is progression of thought. In this book, a theological problem is stated and resolved. The different forms are used in purposeful and judicious ways. It is argued that there is one author, something of an eclectic who borrowed from wisdom and Isaianic traditions, in particular interpreting the latter and anticipating aspects of Isaiah 40-55. The theme of the book is theodicy. This is resolved in the psalm of chapter 3, through the language of prayer. Half the book is expressed in the language of prayer, making it unique among the prophetic books.